El e-business como herramienta de aprendizaje en los estudiantes de la Universidad Técnica de Cotopaxi, de la carrera de ingeniería comercial en el período 2013- 2014 - Soto Romero, David Rogelio (2017)
The following research work details the process carried out for the implementation of E-BUSINESS, as a learning tool, where promoted the use of electronic commerce, in the students of the University "Technique of Cotopaxi" aims to implement E-BUSINESS within the academic plan that promotes educational strategies to facilitate the understanding of various tools of knowledge in educational and professional level. On the theoretical foundation, there are very important issues that are of great help for the development of E - BUSINESS as a learning tool; E-BUSINESS uses powerful tools for the promotion of products and services via the internet in addition that includes a range of online marketing elements. In the exploration of the research allowed define the parameters for the data collection process which will analyze them and take them as an initiative in terms of the methodological specifications as a learning tool, during the investigation the methods used were the deductive, statistical, survey. The most eloquent results of the work are exposed within the conclusions and recommendations are suggestions to the proposal becomes a reality better. The application of this tool therefore plays a very important role, so start a study of new technologies of information, facilitating the improvement of production and transactions.